2017
DOI: 10.1037/pac0000236
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup contact and the potential for post-conflict reconciliation: Studies in Northern Ireland and South Africa.

Abstract: With surveys of Protestants and Catholics in Northern Ireland, and Whites and Blacks in South Africa, this research examines how both contact quality and exposure to intergroup conflict predict attitudes, beliefs, and behaviors relevant to intergroup reconciliation. Across both studies, contact of higher quality predicted more positive intergroup attitudes, trust, more positive perceptions of outgroup intentions in working toward peace, and greater engagement in reconciliation efforts. These effects were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 34 publications
5
61
2
Order By: Relevance
“…Cross‐group friendships may also foster well‐being by creating a collective sense of self‐efficacy among group members, which has been found to be a critical antecedent of collective action tendencies (e.g., Cakal et al ., ; Cocking & Drury, ). Finally, our research also included a strong and positive form of intergroup contact, cross‐group friendship quality, which has been previously demonstrated to have more permanent and positive influences on outgroup attitudes and behaviours (e.g., Tropp, Hawi, et al ., ; Tropp, Mazziotta, et al ., ). It may be interesting to examine whether less powerful or indirect contact experiences also contribute to psychological well‐being through the same mechanisms among minorities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cross‐group friendships may also foster well‐being by creating a collective sense of self‐efficacy among group members, which has been found to be a critical antecedent of collective action tendencies (e.g., Cakal et al ., ; Cocking & Drury, ). Finally, our research also included a strong and positive form of intergroup contact, cross‐group friendship quality, which has been previously demonstrated to have more permanent and positive influences on outgroup attitudes and behaviours (e.g., Tropp, Hawi, et al ., ; Tropp, Mazziotta, et al ., ). It may be interesting to examine whether less powerful or indirect contact experiences also contribute to psychological well‐being through the same mechanisms among minorities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent criticism to the classical intergroup contact theory has been the neglect of contact's unintended consequences, such as reduced motivation for social change (Pettigrew & Hewstone, ; Tropp, Hawi, et al ., ; Tropp, Mazziotta, et al ., Wright & Lubensky, ). This newly emerging research avenue has suggested that contact may create false expectancies about intergroup equality and thereby have some detrimental consequences for minority group members who are likely to display reduced levels of motivation for social change after successful intergroup experiences, a phenomenon that is known as the irony of harmony (e.g., Cakal et al ., ; Dixon et al ., ; Saguy, Tausch, Dovidio, & Pratto, ; Wright & Lubensky, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from the last decade also reveal that positive contact is associated with a greater willingness to forgive among ethnic communities in Bosnia-Herzegovina (Čehajić et al 2008), greater trust toward Palestinians among Jewish Israelis (Maoz and McCauley 2011), and greater forgiveness and trust among religious communities in Northern Ireland (Hewstone et al 2006;Tam et al 2008). Studies with Black and White South Africans, and with Protestants and Catholics in Northern Ireland, also show that friendly, cooperative, and equal status contact with members of the other community predicts not only more positive attitudes and greater trust but also more positive beliefs about the other community's intentions in working toward peace (Tropp et al 2015) .…”
Section: Emotional Processes In Intergroup Contactmentioning
confidence: 99%